PENGARUH KARAKTER DOSEN DAN TEKNIK PEMBELAJARAN TERHADAP MOTIVASI MAHASISWA MENGIKUTI PERKULIAHAN MATEMATIKA EKONOMI DAN BISNIS: Studi pada Mahasiswa STIE ASIA Malang Tahun Ajaran 2015-2016 - Anjaningrum, Widiya Dewi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
This study aims to determine the effect of the character of lecturers and learning techniques to motivate students attending mathematic economics and business lecturing in STIE ASIA Malang academic year 2015/2016. This study is a kind of field research which the data are taken directly from the respondents through questionnaires with Likert scale 1 - 10. The sampling technique that is used in this research is saturation sample (non-probability sampling) which the total sample is 160 students. However, to meet the classical assumptions, it is necessary to remove 5 data, thus, the data that are further processed is 155. The results of the analysis, by SPSS 23 software, shows that the data was valid, reliable and meets the classical assumptions. While the results of multiple linear regression analysis showed that the character of lecturers has positive impact, but it’s not significant to the motivation of students, while learning techniques has positive and significant impact to the student motivation. The contribution ratio of lecturers character with learning techniques to motivate students is 1: 8. Thus, the main thing that is needed to motivate students to be enthusiastic in taking mathematical economics and business lecturing is improving the learning techniques. Improved learning techniques can be done through the delivery of material and exams in the form of a wide range of interesting games that related to the lecturing materials.